The antiradical, phytochemical properties and in vitro cytotoxic activities of Geranium tuberosum subsp. tuberosum - Keser, Serhat; Çelik, Mehmet; Şekerci, Güldeniz; Tekin, Suat; Kaygili, Omer (Niyazi BULUT, 2025)
The genus Geranium, which is important from a medical point of view and whose leaves and tubers are consumed as food, is represented by approximately 400 species distributed especially in temperate regions around the world. One of these species is Geranium tuberosum subsp. tuberosum, a perennial herbaceous species known in our country as “turnagagası” or “devetabanı”. In this study, antiradical, anticancer and phytochemical properties of water, ethanol and methanol extracts of flowers of Geranium tuberosum subsp. tuberosum plant growing in Elazığ were investigated. In vitro antiradical assays were determined against ABTS, DPPH and OH radicals, in vitro anticancer assays were determined against A2780 human ovary, LNCaP human prostate, MCF-7 human breast and Caco-2 human colon cancer cell lines. In addition, the amounts of free fatty acids, fat-soluble vitamins, phytosterols, total phenolics, total flavonoids and total proanthocyanidins contained in this plant were also determined. At the end of the study, it was determined that all extracts of Geranium tuberosum subsp. tuberosum showed lower antiradical properties than the standard antioxidant Trolox in ABTS, DPPH and OH radical scavenging tests. In addition, it was determined that this plant is rich in total phenolics, flavonoids, proanthocyanidins, tocopherols, vitamins D and K, phytosterols and unsaturated fatty acids. According to in vitro anticancer property results, G. tuberosum methanol extracts had the highest anticancer activity against A2780 cell line, and G. tuberosum ethanol extracts had the highest anticancer activity against MCF-7, LNCaP and Caco-2 cell lines.
Keywords: Biochemistry and Cell Biology (Other); Biyokimya ve Hücre Biyolojisi (Diğer)